ANALISIS LAPORAN KEUANGAN DALAM MENGUKUR KINERJA KEUANGAN PADA PT. BUKALAPAK - Ratri Kurniasari; Riskon Ginting; Arizal Putra Pratama (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2023)
This study aims to analyze PT Bukalapak's financial performance for the period 2020 to 2022 by using financial ratios, namely the solvency ratio (debt to equity ratio), activity ratio (total assets turnover), and profitability ratio (return on assets). This type of research is descriptive research that relies on descriptive analysis and elaboration of PT Bukalapak's financial data. It was found that there was an increase in assets in 2021 which occurred due to additional capital from the sale of initial shares causing a decrease in the value of the Debt to Equity Ratio (DER) from 2020 to 2022. From Total Assets Turnover (TAT) there was a decrease in asset turnover in generating profit from 2020 to 2021 and an increase from 2021 to 2022. And the increased Return On Assets (ROA) value illustrates that PT Bukalapak's efforts to increase profit from income on asset management have increased.